The effect of paranet shade on the growth and morphological characteristics in six species of mangrove seedling - Basyuni, Mohammad; Miharza, Try; Sinulingga, Evan Kharogi; Gultom, Epifani Natalia; Djayus, Yunasfi (Penerbit Universiti Kebangsaan Malaysia, 2020)
In mangrove rehabilitation, nursery operation was required to enhance survival of seedlings prior to field planting. Healthy and mature seed and propagules of six mangroves namely Ceriops tagal, Sonneratia alba, Rhizophora apiculata, S. caseolaris, R. mucronata, and Xylocarpus granatum were planted in paranet shade (0%, 25%, 50%, 75% and 100%) for three months. The research purpose was to study the impact of paranet shade on the growth, and morphologic characteristic in all six mangrove seedlings. Results indicated that 50% paranet shade intensity supported C. tagal, R. mucronata, and S. caseolaris seedlings for the best growth (height and diameter). By contrast, 75% intensity of the shade displayed in the optimal growth, number of leaves, and the leaves area of R. apiculata seedlings. We determined that the best growth of seedlings of X. granatum was acquired in the intensity of shade 100%, contrary with S. alba seedling, showing 0% shade intensity as the best for growth. The tolerance to paranet of mangrove shade plants preceded the sequence of X. granatum (landward species) > R. apiculata > R. mucronata; C. tagal, and S. caseolaris > S. alba (seaward species). The present works generates useful information for restoration efforts in North Sumatra and indicates the value for representative mangrove species of intensely shaded nurseries based on optimum growth and morphological characteristics.